Biblioteca escolar do Centro Cultural Brasil Estados Unidos (CCBEU) de Belém (PA): o papel do bibliotecário na prática de ações educativas - SILVA, Andréa de Nazaré Barros da (2017)
It attends the School Library of the United States Cultural Center (CCBEU) in Belém (PA), as well as the role of the librarian in educational practices. So, the possible association between the school library and the professional librarian was analyzed, for the purpose of promote meaningful educational practices that contribute even more to the teaching-learning of the users. Thus, the general objective of the work is to know in loco the (in) existence of the association between the school library and the librarian in the development of educational practices that contribute to the teaching-learning of the users, through a study applied in the CCBEU’s George T. Colman Library in Belém (PA). The specific objectives are to identify the educational practices in which the library is involved and how it develops its functions in this area, to describe the profile of the librarian responsible for the CCBEU library and to verify the pedagogical integration of the George T. Colman Library in the CCBEU. For this, a bibliographic research and an exploratory case study were carried out, through a qualitative approach. By means of the research, it is concluded that the library and the school librarian are indispensable tools for all educational institutions, because both can collaborate with the teaching-learning of the users through educational projects and actions, favoring the access to the information in various formats, and especially, stimulating the liking for reading and research in a relaxed and dynamic way.